Enhancing the Quality of Learning Through Training in PBL and TPACK-Based Teaching Module - Muhmmad Asy’ari; Taufik Samsuri; Laras Firdaus; Saiful Prayogi; Irham Azmi; Mujriah Mujriah; Hunaepi Hunaepi; Akbar Juliansyah; Nova Kurnia; Istin Fitriana Aziza; Helmi Rahmawati (Sasambo: Jurnal Abdimas (Journal of Community Service), 2023)
The goal of the PKM activity is to enhance the quality of learning through intensive training in the creation of teaching modules that integrate the concepts of PBL with the application of TPACK. This reflects the urgency of the teacher's role in adapting the learning approach to the current developments and preparing students to face future challenges. Focusing on the improvement of learning quality provides insights into the importance of integrating PBL and TPACK in innovative and relevant modern learning. The implementation method involves knowledge transfer and the Community Development Model through synchronous and asynchronous online activities. The partners in this activity are students of the PPG Daljab Biology Class of 2023 from the Mandalika University of Education. The activity is carried out for a total of 3 meetings. The results of the activity show that the partners' participation is very active, and there is a significant impact of the training on the partners' understanding of the PBL model and the TPACK approach, as well as their integration into teaching modules